A perovskite solar cell and a method for preparing the same

By using targeted monocrystalline oxidation sub -cave transmission layers, low -defect perovskite photocardiac, oxygen -deficient titanium dioxide electronic transmission layer, and transparent oxide back electrode in the use of targeted single -crystal -growing single crystal -growing The problems of low -infrared radiation utilization, high material prices, poor stability, and low photoelectric conversion efficiency have achieved higher photoelectric conversion efficiency and stability, while reducing manufacturing costs.

CN113314672BActive Publication Date: 2025-01-24JIANGSU UNIV OF SCI & TECH +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202110716857.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-25
Publication Date
2025-01-24
Estimated Expiration
2041-06-25

AI Technical Summary

Technical Problem

Traditional perovskite solar cells have problems such as low infrared radiation utilization, high price of hole transport layer materials, poor stability, and many defects in perovskite absorber layer and low photoelectric conversion efficiency.

Method used

Using single crystal oxidation sub -empty acupoint transmission layers with all directions of heterosexual surface units, oligituctite coatings in low defects are used as an electronic transmission layer as an electronic transmission layer, and transparent oxide conductive electrical film is used as an electronic transmission layer. Back electrode and encapsulate the device.

Benefits of technology

The utilization rate of infrared radiation in sunlight has been improved, the relocation rate, conductivity and device stability are enhanced, and the manufacturing cost is reduced, the efficiency of photoelectric conversion is improved, and the time of the device is delayed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113314672B_ABST
    Figure CN113314672B_ABST
Patent Text Reader

Abstract

The present invention discloses a perovskite solar cell, which relates to the technical field of solar cells, and includes, from bottom to top, a substrate layer, a hole transport layer, a perovskite layer, an electron transport layer, and a back electrode layer. The hole transport layer is a single crystal cuprous oxide film with an anisotropic crystal plane unit, the light absorption layer is a low-defect perovskite material, the electron transport layer is titanium dioxide with oxygen defects, and the back electrode uses a transparent oxide conductive film instead of a traditional metal electrode. The beneficial effect of the present invention is that it has good energy band matching characteristics, realizes the conversion of infrared thermal energy to electrical energy through anisotropic crystal plane units, reduces manufacturing costs, and improves the efficiency and stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, in particular to a perovskite solar cell with infrared thermoelectric conversion capability and a preparation method thereof. Background Art

[0002] At present, energy and environmental pollution problems are becoming increasingly severe, and human beings have an increasing demand for renewable energy. Perovskite has attracted much attention due to its excellent photoelectric properties, such as high absorption coefficient, high carrier mobility, low exciton binding energy, adjustable direct band gap, and simple preparation process. The conversion efficiency of perovskite solar cells has increased from 3.8% in 2009 to 25.5% in 2021. Perovskite solar cells (PSCs) have become one of the most promising new generation photovoltaic devices with broad application prospects.

[0003] Perovskite solar cells include a substrate, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, and a photocathode. In classic perovskite solar cells, infrared light, which accounts for nearly 50% of the total energy of sunlight, cannot be effectively utilized by perovskite solar cells, limiting the further improvement of the photoelectric conversion efficiency of perovskite cells. At present, the technical means to break through this barrier are mainly limited to adding upconversion materials between the electron transport layer and the perovskite light absorbing layer, such as the patent with application number CN202010860888.1. Materials such as Spiro-OMeTAD, PTAA, P3HT, and PEDOT:PSS, which are generally used as hole transport layers, have disadvantages such as high price, low carrier mobility, low conductivity, and poor stability (CN202011350731.0, CN201911306520.4, CN201810898511.8, and CN202010889313.2). The crystal face and surface defects in the perovskite light absorption layer, as well as the interface contact problems, lead to the low efficiency and poor stability of perovskite solar cells. "Anti-solvents" are often used to prepare perovskite solar cells, but the process is complicated and difficult to control (CN201910082871.5). Titanium dioxide (n-TiO2) is a representative electron transport layer of perovskite solar cells (CN201711076827.0), and its carrier density (~10 19 cm -3 ) and mobility (10 -5 ~10 -6 cm 2 / V·s) is relatively low, which hinders the further improvement of the photoelectric conversion efficiency of perovskite solar cells; expensive metals such as gold and silver are generally used to prepare the back electrode (CN201910992919.6); perovskite cells decompose perovskite due to adverse factors such as contact with moisture, oxygen and light during long-term operation, reducing the efficiency and stability of perovskite solar cells. Packaging the components can effectively avoid this problem, but traditional perovskite packaging technology is costly, complex to implement and difficult to use on a large scale, which hinders the further development of perovskite solar cells.

[0004] The application number is CN202010882678.2, and the name is "Solar Cells and Preparation Methods Based on Vacancy Perovskite Materials". A solar cell is disclosed, which includes a metal electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and ITO / FTO, wherein the hole transport layer adopts Spiro-OMeTAD material, and the electron transport layer can adopt a polycrystalline semiconductor. Among them, Spiro-OMeTAD is a traditional polymer hole transport layer, which has problems such as high price (the price per gram exceeds one thousand yuan) and poor stability, while polycrystalline semiconductors have defects such as many grain boundaries, no grid, no orientation, and high impedance. Therefore, the perovskite solar cells developed using the above technology are prone to technical risks such as low conversion efficiency and poor stability; in addition, the general absorption limit of perovskite materials is around 800nm, and they cannot effectively absorb infrared light. Summary of the invention

[0005] Technical issues solved:

[0006] The present invention provides a structure and preparation method of a perovskite solar cell with infrared heat conversion capability. In order to solve the problems of low infrared radiation utilization rate, high hole transport layer material price and poor stability of traditional perovskite solar cells, a single crystal cuprous oxide hole transport layer with anisotropic crystal plane units is grown in situ to replace the traditional organic hole transport layer, and the energy difference between different crystal planes is used to convert part of the infrared heat energy into electrical energy, thereby improving the utilization rate of infrared radiation in sunlight, and reducing the manufacturing cost while improving the hole mobility, conductivity and device stability. In order to solve the problem that the perovskite light absorption layer of solar cells has many defects and low photoelectric conversion efficiency, a perovskite coating in a low defect state is used as the light absorption layer of the solar cell, thereby reducing the influence of the hysteresis effect of the perovskite solar cell. At the same time, titanium dioxide with oxygen defects is used as an electron transport layer to improve the electron mobility, and a transparent oxide conductive film is used to replace the traditional metal back electrode to increase the number of incident photons, reduce the carrier migration distance, and encapsulate the device to improve the device stability and delay its deactivation time.

[0007] Technical solution:

[0008] A perovskite solar cell, wherein a substrate layer, a hole transport layer, a light absorption layer, an electron transport layer and a back electrode layer are stacked in sequence from bottom to top, wherein the electron transport layer is an oxygen-deficient titanium dioxide prepared by a magnetron sputtering method; the oxygen-deficient titanium dioxide n-TiO 2-x The value range of x is 0.01~0.2.

[0009] Preferably, the coating of the anisotropic crystal plane unit is a cuprous oxide single crystal thin film.

[0010] Preferably, the thickness of the hole transport layer is 50 to 500 nm.

[0011] Preferably, the cuprous oxide single crystal film is a single crystal film with a quadrangular pyramid morphology, with an upper surface having exposed {111} crystal planes and a bottom having exposed {100} crystal planes.

[0012] Preferably, n-TiO 2-x The value of x is 0.01~0.2.

[0013] Preferably, the thickness of the electron transport layer is 10 to 150 nm.

[0014] Preferably, in the low-defect state of iodine lead methylamine, the molar ratio of methylammonium iodide to lead iodide during the preparation process is greater than 1.

[0015] A method for preparing a perovskite solar cell, characterized in that it comprises the following steps:

[0016] Step 1: substrate pretreatment: polish the substrate surface with nano-diamond slurry and wool polishing pad, ultrasonically clean with acetone and ethanol in turn to remove surface impurities, and dry with high-pressure argon gas for standby use;

[0017] Step 2: Directed growth of a hole transport layer; preparing a copper ion solution, adjusting the pH, and in-situ directed growth of a single crystal cuprous oxide hole transport layer having a crystal plane orientation characteristic by an electrochemical deposition method;

[0018] Step 3: coating of the perovskite layer; preparing a perovskite precursor solution by adding an excess of methylammonium iodide, and coating the perovskite layer by a one-step spin coating method, a blade coating method, a Czochralski method, or a spray coating method;

[0019] Step 4: magnetron sputtering oxygen-deficient titanium dioxide electron transport layer;

[0020] Step 5: Prepare the back electrode of the solar cell by physical vapor deposition;

[0021] Step 6: Encapsulate the perovskite solar cell with a hydrophobic polymer.

[0022] Beneficial effects of the present invention: The present invention adopts a single-crystal cuprous oxide film with anisotropic crystal plane units grown in a directional manner as a hole transport layer, a precursor solution prepared with excess methylammonium iodide, a perovskite light absorption layer prepared by a one-step spin coating method, a scraping method, a pulling method or a spray coating method, an oxygen-deficient titanium dioxide as an electron transport layer, and a transparent conductive oxide as a back electrode, and encapsulates the perovskite solar cell through a hydrophobic polymer. The perovskite solar cell device has infrared thermoelectric conversion capability, improved stability and can be applied on a large scale, and has obvious advantages such as simple operation and low cost; the electron transport layer of the present invention has significantly improved electron extraction and transportation performance, which is about four orders of magnitude greater than that of traditional titanium dioxide films, so that photogenerated electrons are more effectively attracted to the oxygen-deficient titanium dioxide (n-TiO 2-x ) electron transport layer; the electron transport layer of the present invention produces obvious gain effects, including: increased filling factor, increased short-circuit current, increased conversion efficiency, etc.; different from the previous pickling technology which can only perform oxygen-deficient treatment on the surface semiconductor, the magnetron sputtering technology used in the present invention can make the oxygen-deficient titanium dioxide form a uniform, dense, and overall oxygen-deficient n-TiO 2-x The oxygen deficiency concentration in the film can be precisely controlled. 2-x The value range of x in the film is 0.01-0.2. When x is less than 0.01, the oxygen deficiency concentration is too low, and the crystal structure and semiconductor properties gradually approach intrinsic TiO2. When x is greater than 0.2, the oxygen deficiency concentration is too high, which will cause the destruction of the crystal structure and the overall performance of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell of the present invention;

[0024] Figure 2 This is a scanning electron microscope photo of the hole transport layer used in the present invention;

[0025] Figure 3 The electron microscope, X-ray diffraction spectrum, and impedance spectrum comparison diagram of the low-defect perovskite layer of the present invention and the ordinary perovskite layer, wherein (a) is insufficient MAI, (b) is equal to MAI, and (c) is excessive MAI;

[0026] Figure 4 This is a current-voltage test curve of the perovskite solar cell of the present invention.

[0027] Among them: 1-base layer, 2-cuprous oxide hole transport layer, 3-perovskite light absorption layer, 4-oxygen-deficient titanium dioxide electron transport layer, 5-back electrode layer. DETAILED DESCRIPTION

[0028] The present invention provides a perovskite solar cell with infrared thermoelectric conversion function and a method for preparing the same. In order to make the purpose, technical solution and effect of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments.

[0029] Embodiment 1:

[0030] Nano diamond slurry and relatively soft wool polishing pad were used to polish the 2×2 cm 2 , the ITO (7Ω / cm) coated glass substrate with a thickness of 1.1mm was pre-polished, and then cleaned with detergent powder, acetone, ethanol, and deionized water under ultrasonic cleaning for 10 minutes to remove organic and inorganic impurities on the surface, and then dried with high-pressure argon. 1.2g of copper sulfate, 10ml of sodium lactate and 0.152g of sodium tetraborate were dissolved in 40ml of deionized water solution, magnetically stirred until fully dissolved, and a 1M sodium hydroxide solution was gradually added dropwise to adjust the pH of the plating solution to 8.5. A water bath with a temperature probe was used to maintain the bath temperature at 20°C, and a conductive glass was used as the negative electrode and a metal platinum electrode was used as the positive electrode. A constant voltage of 1.2V was applied for electrodeposition. Subsequently, the cuprous oxide film was repeatedly rinsed with deionized water and quickly dried in a high-pressure argon gas flow. Finally, a single-crystal cuprous oxide film with anisotropic crystal plane units and infrared heat conversion function grown along the {100} direction was obtained. From the scanning microscope photos, it can be seen that the surface of the film is composed of countless tetrahedral pyramids, each of which exposes 4 {111} crystal planes.

[0031] The perovskite layer was prepared by a one-step spin coating method. Methylammonium iodide (CH3NH3I) and lead iodide (PbI2) were dissolved in a mixed solvent of N,N-dimethylformamide / dimethyl sulfoxide (7:3v / v) at a molar ratio of 1.05:1 to prepare a mixed halide perovskite precursor solution with a concentration of 1M. It was directly spin-coated on the surface of the cuprous oxide single crystal film at a speed of 4000rpm for 5s. During the spin coating, chlorobenzene was added as an antisolvent to promote the crystallization and crystal transformation of the perovskite material. Heated at 100℃ for 5min, the light yellow transparent film was transformed into a brown-black perovskite film.

[0032] The vacuum chamber was pre-evacuated to 1.0×10 -4 Pa base pressure, high purity argon as the working gas, using a 50 mm diameter n-TiO 2-x The target (purity: 99.99%) was deposited with a 20 nm thick n-TiO layer by a DC magnetron sputtering apparatus at a constant working pressure of 0.3 Pa. 2-x Electron transport layer.

[0033] The vacuum chamber was pre-evacuated to 1.0×10 -4Pa base pressure, high-purity argon as the working gas, using a FTO target with a diameter of 50 mm (purity: 99.99%), and a DC magnetron sputtering instrument to deposit a 50 nm thick FTO photocathode at a constant working pressure of 0.3 Pa.

[0034] The EVA film was heated at 150°C to polymerize the EVA, and the EVA film and the perovskite cell module were bonded together under an argon atmosphere to prevent moisture and the atmospheric environment from damaging the perovskite solar cells.

[0035] Embodiment 2:

[0036] To prepare flexible perovskite solar cells, a 20×30 cm2 sheet was cleaned with detergent powder, acetone, ethanol, and deionized water under ultrasonic cleaning. 2 The soft polycarbonate (PC) substrate was cleaned for 10 min to remove organic and inorganic impurities on the surface and then dried with high-pressure argon gas.

[0037] The vacuum chamber was pre-evacuated to 1.0×10 -4 The ITO conductive layer was deposited by a DC magnetron sputtering apparatus at a base pressure of 0.3 Pa, with high-purity argon as the working gas and an ITO target with a diameter of 50 mm (purity: 99.99%).

[0038] Dissolve 1.2g of copper sulfate, 10ml of sodium lactate and 0.152g of sodium tetraborate in 40ml of deionized water solution, stir magnetically until fully dissolved, and gradually add 1M sodium hydroxide solution to adjust the pH of the plating solution to 8.5. Use a water bath with a temperature probe to maintain the bath temperature at 20°C, use conductive glass as the negative electrode and a metal platinum electrode as the positive electrode, apply a 1.2V constant voltage electrodeposition, then repeatedly rinse the cuprous oxide film with deionized water and quickly dry it in a high-pressure argon gas flow. Finally, a single-crystalline cuprous oxide film grown along the {100} direction was obtained. From the scanning microscope photo, it can be seen that the surface of the film is composed of countless tetrahedral pyramids, each of which exposes 4 {111} crystal faces.

[0039] The perovskite layer was prepared by spraying. Methylammonium iodide (CH3NH3I) and lead iodide (PbI2) were dissolved in a mixed solvent of N,N-dimethylformamide / dimethyl sulfoxide (9:1v / v) at a molar ratio of CH3NH3I and PbI2 of 1.2:1 to prepare a mixed halide perovskite precursor solution with a concentration of 0.8M. The solution was sprayed on the surface of the cuprous oxide single crystal film for 5s by a spray gun, during which methyl benzoate was added as an antisolvent to promote the crystallization and crystal transformation of the perovskite material. The light yellow transparent film was transformed into a brown-black perovskite film by heating at 120℃ for 5min.

[0040] The vacuum chamber was pre-evacuated to 1.0×10-4 Pa base pressure, high purity argon as the working gas, using a 50 mm diameter n-TiO 2-x The target (purity: 99.99%) was deposited by DC magnetron sputtering at a constant working pressure of 0.3 Pa. 2-x Electron transport layer.

[0041] The solar cell photocathode was prepared by vacuum evaporation. The vacuum chamber was pre-evacuated to 1.0×10 -4 A Ag target (purity: 99.99%) with a diameter of 2 mm was used at a base pressure of 1.5 Pa, and a direct voltage was applied to evaporate it onto the surface of the electron transport layer to prepare an Ag photocathode.

[0042] The sticky urethane acrylate (UA) is dropped onto the surface of the photocathode and spun at high speed (>10000rpm), and then the sample is placed under a high-power UV lamp. The spin-coated monomer UA film polymerizes to form solid polyurethane acrylate (PUA) to encapsulate the cell to prevent moisture and atmospheric environment from damaging the perovskite solar cell.

[0043] Embodiment 3:

[0044] Size: 2 x 2 cm 2 , an ITO (7Ω / cm) coated glass substrate with a thickness of 1.1 mm was pre-polished, and then cleaned with detergent powder, acetone, ethanol, and deionized water under ultrasonic cleaning for 10 min to remove surface organic and inorganic impurities, and then dried with high-pressure argon gas.

[0045] The vacuum chamber was pre-evacuated to 1.0×10 -4 Pa base pressure, high purity argon as the working gas, using a 50 mm diameter n-TiO 2-x The target (purity: 99.99%) was deposited with a DC magnetron sputtering apparatus at a constant working pressure of 0.3 Pa to deposit a 30 nm thick n-TiO 2-x Electron transport layer.

[0046] The perovskite light-absorbing layer was prepared by a doctor blade coating method. Methylammonium iodide (CH3NH3I) and lead iodide (PbI2) were dissolved in a mixed solvent of N,N-dimethylformamide / dimethyl sulfoxide (8:2 v / v) at a molar ratio of CH3NH3I to PbI2 of 1.1:1 to prepare a 1M mixed halide perovskite precursor solution. 2-x The substrate was then scraped off with an air knife to obtain a uniform and flat MAPbI3 precursor film. The light yellow transparent film was transformed into a brown-black perovskite film by heating at 150°C for 5 minutes.

[0047] 9.9 μL of 0.25 M FK209-acetonitrile solution, 9.6 μL of 1.8 M Li-TFSI-acetonitrile solution, and 14.3 μL of tBP were added to 500 μL of chlorobenzene to prepare an 85 mg / mL Spiro-OMeTAD solution, which was spin-coated on the perovskite layer at 4000 rpm for 30 s to prepare a Spiro-OMeTAD hole transport layer.

[0048] The vacuum chamber was pre-evacuated to 1.0×10 -4 The FTO photocathode was deposited by a DC magnetron sputtering apparatus at a constant working pressure of 0.3 Pa, with high-purity argon as the working gas and a FTO target with a diameter of 50 mm (purity: 99.99%).

[0049] The EVA film was heated at 150°C to polymerize the EVA, and the EVA film and the perovskite cell module were bonded together under an argon atmosphere to prevent moisture and the atmospheric environment from damaging the perovskite solar cells.

[0050] The present invention discloses a perovskite solar cell having a structure as follows: Figure 1 As shown. If the electron transport layer is prepared by conventional spin coating, only a single titanium dioxide (n-TiO2) thin film can be obtained, which has a single structure and function, and the titanium-oxygen molar ratio cannot be adjusted, which greatly limits the physical and chemical properties of titanium dioxide. 2-x ) film, the oxygen defect concentration inside titanium dioxide can be artificially controlled, and it is used for the first time in perovskite solar cells. Compared with the traditional titanium dioxide (n-TiO2) film, the oxygen-deficient titanium dioxide (n-TiO 2-x ) film has higher carrier mobility and higher conductivity, which is not achievable by conventional titanium dioxide films. As shown in Table 1, the oxygen-deficient titanium dioxide (n-TiO 2-x ) as the electron transport layer 4, the electron extraction and transport performance is significantly improved, about four orders of magnitude greater than that of the traditional titanium dioxide film, so that the photogenerated electrons are more effectively attracted to the oxygen-deficient titanium dioxide (n-TiO 2-x ) electron transport layer 4. As shown in Table 2, oxygen-deficient titanium dioxide (n-TiO 2-x ) film as the electron transport layer 4, which produces obvious gain effects, including: increased filling factor, increased short-circuit current, increased conversion efficiency, etc. 2-x ) film as the electron transport layer 4, preferably with a thickness of 20 to 150 nm; in addition, density functional theory (DFT) calculations confirm that magnetron sputtered oxygen-deficient titanium dioxide (n-TiO 2-x) film provides a more ideal band structure than traditional titanium dioxide.

[0051] Table 1 Electrochemical properties of different electron transport layers

[0052]

[0053] The cuprous oxide prepared by the traditional method is a polycrystalline film without orientation and crystal face anisotropy, and has a single structure and function. The present invention adopts the electrochemical growth method to grow a cuprous oxide single crystal film with anisotropic crystal face characteristics. The scanning electron microscope photo is as follows: Figure 2 As shown, the surface exposes the {111} crystal plane (A), and the bottom is the {100} crystal plane (B), which has significant structural and performance differences from the traditional cuprous oxide film. As shown in Table 3, the single-crystal cuprous oxide film used in the present invention has higher hole conductivity and mobility. The cuprous oxide single-crystal film with anisotropic crystal plane units used in the present invention has many characteristics and advantages such as carrier self-separation, thermoelectric conversion, and photoelectric conversion, which are also not possessed by the previous polycrystalline cuprous oxide films. After the cuprous oxide single-crystal film with the anisotropic crystal plane unit is used as the hole transport layer in the perovskite solar cell, a significant gain effect is produced, including: an increase in open circuit voltage, an increase in short-circuit current, an increase in conversion efficiency, etc., as shown in Table 2. The cuprous oxide single-crystal film is used as the hole transport layer 2, and the thickness is preferably 50 to 500 nm. Compared with traditional organic materials such as Spiro-OMeTAD, PTAA, P3HT, PEDOT:PSS, etc., it solves the problems of high price and poor stability of the hole transport layer. At the same time, the anisotropic crystal plane unit can spontaneously separate the charges between the crystal planes, convert part of the thermal energy of infrared radiation into electrical energy, and improve the hole mobility and conductivity.

[0054] Table 2 Photovoltaic performance of solar cells prepared using different electron transport layers, hole transport layers and cathodes

[0055]

[0056] Spectrum: AM 1.5G spectrum (200<λ<2500nm); p-Cu2O ACFU: Cuprous oxide with anisotropic crystal surface characteristics

[0057] The present invention uses excessive methylammonium iodide (MAI) to promote the crystallization of perovskite, generate a uniform, smooth and dense perovskite film, obtain a perovskite film with very few crystal defects, crystal cracks and holes, enhance the photoelectric conversion ability of perovskite, and delay the deactivation time of perovskite. The traditional preparation method emphasizes the preparation method of equal or small amount of methylammonium iodide (MAI), which is essentially different from the present invention. Figure 3As shown, compared with the perovskite film synthesized in the traditional ratio, the low-defect perovskite film improves the crystal quality and AC impedance of the device and reduces the influence of the hysteresis effect, which is not available in the previous perovskite film. In the past, it was generally necessary to adopt the restricted space growth method to obtain low-defect perovskite materials. This method is time-consuming and difficult to achieve controllable growth. The low-defect perovskite material synthesized by the excessive MAI (MAI:PbI2=1.01~1.2) technical method adopted in the present invention is to coat the perovskite layer on the hole transport layer by a one-step spin coating method or a spray coating method. The thickness of the perovskite layer is preferably 300~1200nm, which well compensates for the disadvantages of the previous technology in cost and process difficulty.

[0058] In the present invention, the substrate (1) is a metal electrode or an inorganic non-metallic conductive film, preferably any one of indium tin oxide conductive glass (ITO), aluminum-doped zinc oxide conductive glass (AZO), fluorine-doped tin oxide conductive glass (FTO), gallium-doped zinc oxide conductive glass (GZO), and indium zinc oxide conductive glass (IZO) or a combination thereof. The back electrode (5) is a transparent inorganic oxide conductive film, preferably any one of fluorine-doped tin oxide (FTO), indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), and indium zinc oxide (IZO). The back electrode (5) is prepared by magnetron sputtering technology, and the thickness is preferably 80 to 120 nm. Compared with the traditional metal wire electrode, the inorganic oxide electrode avoids the possibility of metal ion diffusion leading to perovskite light absorption layer contamination and open circuit voltage reduction. The back electrode replaces the traditional metal wire electrode, increases the electrode contact area, reduces the carrier migration distance while reducing the preparation cost, increases the number of incident photons, and helps to improve the photoelectric conversion efficiency of the device. The perovskite solar cell is encapsulated by a hydrophobic polymer, wherein the hydrophobic polymer is one or more of ethylene vinyl acetate (EVA), polyurethane acrylate (PUA), polyvinyl butyral (PVB), thermoplastic polyurethane (TPD), polyethylene (PE), polyvinyl chloride (PVC), and polypropylene (PP).

[0059] Table 3 Electrochemical properties of different hole transport layers

[0060]

[0061] Depend on Figure 4 It can be seen that due to the irradiation of infrared rays in the solar spectrum, the temperature of the solar cell rises from 32 degrees Celsius to 55 degrees Celsius. The solar cell disclosed in the present invention converts part of the thermal energy into electrical energy output. As the temperature rises, the overall energy conversion efficiency is also improved by 3%, proving its infrared thermoelectric conversion capability.

[0062] The basic principles, main features and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed for protection.

Claims

1. A perovskite solar cell, wherein a substrate layer, a hole transport layer, a light absorbing layer, an electron transport layer and a back electrode layer are stacked in sequence from bottom to top, characterized in that: The electron transport layer is an oxygen-deficient titanium dioxide prepared by magnetron sputtering; the oxygen-deficient titanium dioxide n-TiO 2-x The value range of x is 0.01 to 0.2; wherein the light absorbing layer adopts a perovskite layer in a low-defect state; the perovskite layer in a low-defect state is methylamine iodide, and the molar ratio of methylammonium iodide to lead iodide in the preparation process is greater than 1; the hole transport layer is a coating with anisotropic crystal plane units, and the coating of the anisotropic crystal plane units is a cuprous oxide single crystal film; a single crystal cuprous oxide hole transport layer with crystal plane orientation characteristics is in-situ directionally grown by an electrochemical deposition method.

2. A perovskite solar cell according to claim 1, characterized in that: In order to match the hole transport effect with the overall resistance, the thickness of the hole transport layer is 50 to 500 nm.

3. A perovskite solar cell according to claim 1, characterized in that: The cuprous oxide single crystal film is a single crystal film in the shape of a quadrangular pyramid, with an exposed {111} crystal plane on the upper surface and an exposed {100} crystal plane on the bottom.

4. A perovskite solar cell according to claim 1, characterized in that: In order to achieve excellent electron transport performance and light transmittance, the thickness of the electron transport layer is preferably 10 to 150 nm.

5. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The steps include: Step 1: substrate pretreatment: polish the substrate surface with nano-diamond slurry and wool polishing pad, ultrasonically clean with acetone and ethanol in turn to remove surface impurities, and dry with high-pressure argon gas for standby use; Step 2: Directed growth of a hole transport layer; preparing a copper ion solution, adjusting the pH, and in-situ directed growth of a single crystal cuprous oxide hole transport layer having a crystal plane orientation characteristic by an electrochemical deposition method; Step 3: coating of the perovskite layer; preparing a perovskite precursor solution by adding an excess of methylammonium iodide, and coating the perovskite layer by a one-step spin coating method, a blade coating method, a Czochralski method, or a spray coating method; Step 4: magnetron sputtering oxygen-deficient titanium dioxide electron transport layer; Step 5: Prepare the back electrode of the solar cell by physical vapor deposition; Step 6: Encapsulate the perovskite solar cell with a hydrophobic polymer.

Citation Information

Patent Citations

  • Titanium-dioxide electron transport layer for perovskite solar cell and preparation method thereof

    CN107919438A

  • A perovskite solar cell with P3HT / graphene as the hole transport layer and its fabrication method.

    CN109216554B

  • A method for preparing perovskite thin films based on reverse solution bath and a solar cell

    CN109904318B

  • Perovskite solar cell and preparation method thereof

    CN110783464A

  • A perovskite solar cell and its fabrication method

    CN110931645B